Molecular Evidence for Functional Divergence and Decay of a Transcription Factor Derived from Whole-Genome Duplication in Arabidopsis thaliana . Issue 4 (23rd June 2015) - Lehti-Shiu, Melissa D.; Uygun, Sahra; Moghe, Gaurav D.; Panchy, Nicholas; Fang, Liang; Hufnagel, David E.; Jasicki, Hannah L.; Feig, Michael; Shiu, Shin-Han
Abstract : Functional decay of a transcription factor retained after whole-genome duplication suggests that duplicate gene loss is a prolonged process occurring over tens of millions of years. Abstract: Functional divergence between duplicate transcription factors (TF s) has been linked to critical events in the evolution of land plants and can result from changes in patterns of expression, binding site divergence, and/or interactions with other proteins. Although plant TF s tend to be retained post polyploidization, many are lost within tens to hundreds of million years. Thus, it can be hypothesized that some TF s in plant genomes are in the process of becoming pseudogenes. Here, we use a pair of salt tolerance-conferring transcription factors, DWARF AND DELAYED FLOWERING1 ( DDF1 ) and DDF2, that duplicated through paleopolyploidy 50 to 65 million years ago, as examples to illustrate potential mechanisms leading to duplicate retention and loss. We found that the expression patterns of Arabidopsis thaliana ( At ) DDF1 and AtDDF2 have diverged in a highly asymmetric manner, and AtDDF2 has lost most inferred ancestral stress responses. Consistent with promoter disablement, the AtDDF2 promoter has fewer predicted cis-elements and a methylated repetitive element. Through comparisons of AtDDF1, AtDDF2, and their Arabidopsis lyrata orthologs, we identified significant differences in binding affinities and binding site preference. In particular, an AtDDF2-specific substitution within the DNA-binding domain significantly reduces binding affinity. Cross-species analyses indicate that both AtDDF1 and AtDDF2 are under selective constraint, but among A. thaliana accessions, AtDDF2 has a higher level of nonsynonymous nucleotide diversity compared with AtDDF1 . This may be the result of selection in different environments or may point toward the possibility of ongoing functional decay despite retention for millions of years after gene duplication.